DAMPAK PERANG RUSIA-UKRAINA : TINJAUAN PENGARUH PERGERAKAN HARGA MINYAK DAN NIKEL TERHADAP SUKU BUNGA DI INDONESIA - Dedy; Adot, Natalia (Mount Hope Management International Journal, 2024)
One of the factors that causes increasing commodity prices in recent years is motivated by the Russia-Ukraine war since 2022. Russia is one of the world’s producers, especially for petroleum and mining industries such as nickel, aluminum, and palladium, so that commodity prices have also increased significantly and each world government will take its own policies in accordance with the impact of the war. The pupose of this study is to determine the influence of world oil and nickel price volatilities on interes rate policy in Indonesia. The method of this study uses a quantitative approach with multiple linear regression as the analysis techniques. The data source is in the form of secondary data obtained on a monthly basis from 2022 – 2024 in accordance with the volatilities of each variable. The results show that the oil prices have an influence but are negative on interest rates, as well as nickel prices also have an influence and negative on interest rate. Simultaneously, both of variables affect interest rates.